Correlates of physical disability in the elderly population of Rural North India (Haryana) - Zahid A Khan (Journal of Family and Community Medicine, 2018)
Background: With the increase in life expectancy, the number of older persons is constantly rising. Disability rates for elderly people are also on the rise with an increase in the burden of chronic diseases depriving them of independence and the performance of activities of daily living. The study aimed to estimate the prevalence of physical disability and determine its correlates among elderly population of rural Haryana. Materials and Methods: A community-based cross-sectional study was conducted among 322 elderly participants aged 60 years and above in the rural area of Haryana, India. Data pertaining to sociodemographic profile, self-reported chronic diseases/ailments, and disability assessment by means of Barthel and Katz index of activities of daily living was collected and analyzed. Results: Overall, 21.4% and 18% elderly people had some form of disability according to the Barthel index and Katz index, respectively. With aging, disability increased and 52.5% of the elderly aged 75 years and above were found to have disability according to the Barthel's index. Females (P = 0.014), those who were currently not married (P = 0.001), currently unemployed (P = 0.001), and those with chronic diseases/ailments (P = 0.002), had significantly higher disability rates. Binary logistic regression analysis revealed age 75 years and above, current unemployment, and the presence of three or more chronic diseases/ailments as significant factors related to physical disability. Conclusion: Disability is associated with increasing age and an increase in the burden of chronic health ailments in the elderly. Consequently, there is the need to prioritize preventive, promotive, curative, and rehabilitative services for the geriatric population.